Endogenous advanced glycation end products in the pathogenesis of chronic diabetic complications - Mengstie, Misganaw Asmamaw; Chekol Abebe, Endeshaw; Behaile Teklemariam, Awgichew; Tilahun Mulu, Anemut; Agidew, Melaku Mekonnen; Teshome Azezew, Muluken; Zewde, Edgeit Abebe; Agegnehu Teshome, Assefa (Frontiers in Molecular Biosciences, 2022)
Diabetes is a common metabolic illness characterized by hyperglycemia and is linked to long-term vascular problems that can impair the kidney, eyes, nerves, and blood vessels. By increasing protein glycation and gradually accumulating advanced glycation end products in the tissues, hyperglycemia plays a significant role in the pathogenesis of diabetic complications. Advanced glycation end products are heterogeneous molecules generated from non-enzymatic interactions of sugars with proteins, lipids, or nucleic acids via the glycation process. Protein glycation and the buildup of advanced glycation end products are important in the etiology of diabetes sequelae such as retinopathy, nephropathy, neuropathy, and atherosclerosis. Their contribution to diabetes complications occurs via a receptor-mediated signaling cascade or direct extracellular matrix destruction. According to recent research, the interaction of advanced glycation end products with their transmembrane receptor results in intracellular signaling, gene expression, the release of pro-inflammatory molecules, and the production of free radicals, all of which contribute to the pathology of diabetes complications. The primary aim of this paper was to discuss the chemical reactions and formation of advanced glycation end products, the interaction of advanced glycation end products with their receptor and downstream signaling cascade, and molecular mechanisms triggered by advanced glycation end products in the pathogenesis of both micro and macrovascular complications of diabetes mellitus.